Spatial distributions and co-occurrence of New Zealand shallow reef urchins : a thesis presented in partial fulfilment of requirements for the degree of Master of Biological Science, at Massey University, Albany, New Zealand - Simpson, Thomas William (Massey University, 2021)
Globally, ecosystems are experiencing significant disruption due to unprecedented environmental changes. These environmental changes result in many species undergoing range shifts, creating a series of novel interspecies interactions. These changes have significantly affected several ecosystems; temperate kelp forests have seen an influx of tropical and sub-tropical herbivores resulting in many being damaged by overgrazing. Here, in chapter II I examine the drivers of variability in the abundance of three such sub-tropical grazers, the shallow reef urchin species Centrostephanus rodgersii, Heliocidaris tuberculata, and Tripneustes kermadecensis at Rangitāhua. I assessed the patterns of abundance for the urchin species, using a generalized linear mixed model, investigating relationships between abundance and three variables (Depth, topographical complexity, and algal composition) and the other species' abundance. The models show the three species being most abundant in unique combinations of variables. Significant correlations were observed between C. rodgersii and the other species (negative at the site level for T. kermadecensis and positive at the transect level for H. tuberculata) suggesting microhabitat segregation among the species. In chapter III, I then model the present and future distribution of four urchin species present in New Zealand; the three subtropical species listed above, and the endemic kina (Evechinus chloroticus). I modelled the urchin's present and future distributions using four different species distribution modelling techniques, Generalized Linear Models, Maximum Entropy, Random Forests, and Support Vector Mechanics, to create an ensemble model of their distributions. I then created future models for four of the Representative Concentration Pathway (RCP) future climate scenarios for 2100, ranging from optimistic (RCP 2.6) to worst-case (RCP 8.5). The models predict poleward range shifts in all three subtropical species, under all future climate scenarios, with the range shifts' extent depending on climate change severity. Although no range shift was predicted in E. chloroticus, a reduction in environmental suitability was predicted. The range expansions of these urchins along north-eastern New Zealand's coast will bring them into increased contact with kina and New Zealand's kelp forests. Changes in the urchin populations could devastate New Zealand's kelp forests and better understanding is required if preemptive conservation management is to be applied.
Keywords: 410102 Ecological impacts of climate change and ecological adaptation